2001
DOI: 10.1590/s1517-86922001000500003
|View full text |Cite
|
Sign up to set email alerts
|

Potência muscular máxima na flexão do cotovelo uni e bilateral

Abstract: os da execução bilateral, a CM era 5% maior (p = 0,02) e a PM 5% menor (p = 0,053). Conclusão: Apesar de todos serem destros, não houve diferenças unilaterais em CM e PM, provavelmente devido à inexperiência nesse exercício (fatores neurais). A soma dos resultados unilaterais difere em 5% daquele obtido bilateralmente, mostrando, contudo, tendências opostas entre PM e CM, provavelmente refletindo uma limitação central na coordenação motora de um movimento complexo feito em máxima velocidade e com carga relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
1
19
1
2
Order By: Relevance
“…This episode was probably reached by greater neural drive for the non-dominant limb, by the existence of possible deficiencies in the intermuscular coordination levels during movement, causing greater recruiting of motor units. Opposite data were found by Simão et al 9,10 and Chaves et al 11 , in which unilateral differences were not observed in load and maximum muscular power 6 . Some considerations must be mentioned concerning our findings.…”
Section: Contractionmentioning
confidence: 67%
See 1 more Smart Citation
“…This episode was probably reached by greater neural drive for the non-dominant limb, by the existence of possible deficiencies in the intermuscular coordination levels during movement, causing greater recruiting of motor units. Opposite data were found by Simão et al 9,10 and Chaves et al 11 , in which unilateral differences were not observed in load and maximum muscular power 6 . Some considerations must be mentioned concerning our findings.…”
Section: Contractionmentioning
confidence: 67%
“…When load, power and maximum repetitions until exhaustion are analyzed, Simão et al 9,10 and Chaves et al 11 verified the existence of bilateral deficit related to maximal load, but the same episode did not occur with maximal muscular power 9 . It is supposed that uni and bilateral maximal contractions are characterized concerning their neuromuscular activation, by the recruiting of many muscular groups or in many frequencies through a parallel process of intermuscular coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Participants performed 6-10 warm-up repetitions with approximately 50% of the load that would be used on the first trial of each test session (15). The assessment was started two minutes after warm-up.…”
Section: Methodsmentioning
confidence: 99%
“…Esses receptores estão localizados próximos às inserções ósseas que influenciam a capacidade contrátil da musculatura extensora, e reduzem a capacidade de contração durante a realização de exercícios, visto que a musculatura do quadríceps encontra-se atrofiada no período pós-cirúrgico [6][7][8] . Alguns autores destacam que indivíduos saudáveis demonstram a força desenvolvida durante ações bilaterais, normalmente menor do que a soma da força desenvolvida por cada membro [9][10][11][12][13] . No entanto, até o presente momento, não foi verificado na literatura nenhum estudo abordando o déficit bilateral em indivíduos durante o período pós-cirúrgico de LCA.…”
Section: Introductionunclassified
“…Em contraposição, Simão et al 10 estudaram o déficit bilateral na carga máxima e na potência muscular máxima em um teste de 1RM, no movimento de flexão de cotovelo, sendo verificadas diferenças significativas apenas quando comparado o SU com as cargas obtidas bilateralmente relacionados à 1RM, não sendo evidenciadas diferenças significativas na comparação entre os membros. Não foram verificadas diferenças para a potência muscular, demonstrando não ocorrer o déficit bilateral em trabalhos com velocidades elevadas.…”
unclassified